Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This problem has to do with a canonical transformation and Hamiltonian formalism. Below is my attempt at solving it, but I am not too sure about it. Please help!

Let $\theta$ be some parameter.

And $$X_1=x_1\cos \theta-y_2\sin\theta\\ Y_1=y_1\cos \theta+x_2\sin\theta\\ X_2= x_2\cos \theta-y_1\sin\theta\\ Y_2=y_2\cos\theta+x_1\sin \theta $$

Suppose the original Hamiltonian is $$H(x,y)={1\over 2}(x_1^2+y_1^2+x_2^2+y_2^2)$$ I wish to find solve for the motion in terms of the new variables. I am also given the restriction that $X_2=Y_2=0$


I believe we have $$H(X,Y)={1\over 2}(X_1^2+Y_1^2+X_2^2+Y_2^2)$$

Now the normal Hamiltonian formalism would suggest that $$\dot X_i={\partial H\over \partial Y_i }\\ \dot Y_i=-{\partial H\over \partial X_i }$$

Which gives $$\ddot X_1=-X_1\\ \ddot Y_1=-Y_1$$ Therefore, $$X_1(t)=A(\theta)\cos t+B(\theta)\sin t\\ Y_2(t)=C(\theta)\cos t+D(\theta)\sin t$$*Is this form of solutions right?*

We see that the $${\partial X_1\over \partial \theta}=-Y_2=0\\ {\partial Y_1\over \partial \theta}=X_2=0$$ So $A,B,C,D$ must be constants.

Are these arguments right? And can I get a better solution, say by getting a more specific set of $A,B,C,D$, given only the given information?

Thank you.

share|cite|improve this question
You've conflated the problem and the solution; it's not clear where the problem statement ends and your solution attempt begins. – joriki Dec 30 '12 at 3:06
Dear @joriki , I have edited the question. Hopefully it is of better form now. – Morgan Dec 30 '12 at 3:19

Almost there. First, you made a typo: you mean to write $Y_1(t)$, not $Y_2(t)$, for the expression $C(\theta)\cos t + D(\theta)\sin t .$

Finally, knowing $\dot X_1 = {\partial H \over \partial Y_i}$, you obtain $$ -A \sin t + B \cos t = Y_1 = C \cos t + D \sin t. $$ And the equation for $\dot Y_1$ yields (redundantly) $$ -C \sin t + D \cos t = - A \cos t - B \sin t. $$ This means $$ X_1(t) = A \cos t + B \sin t, \qquad Y_1(t) = B \cos t - A \sin t. $$ This is a parametrization of a circle with radius $\sqrt{A^2 + B^2}$ in the $(X_1,Y_1)$ plane.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.